Hysteretic energy spectrum and damage control. - Riddell, Rafael (Earthquake engineering & structural dynamics.)
The inelastic response of single degree of freedom (SDOF) systems subjected to earthquake motions is studied and a method to derive hysteretic energy dissipation spectra is proposed. The amount of energy dissipated through inelastic deformation combined with other response parameters allow the estimation of the required deformation capacity to avoid collapse for a given design earthquake. In the first part of the study, a detailed analysis of correlation between energy and ground motion intensity indices is carried out to identify the indices to be used as scaling parameters and base line of the energy dissipation spectrum. The response of elastoplastic, bilinear, and stiffness degrading systems with 5 percent damping, subjected to a world wide ensemble of 52 earthquake records is considered. The statistical analysis of the response data provides the factors for constructing the energy dissipation spectrum as well as the Newmark Hall inelastic spectra. The combination of these spectra allows the estimation of the ultimate deformation capacity required to survive the design earthquake, capacity that can also be presented in spectral form as an example shows.